(untitled) (Jurnal Bahasa, 2012)
This study describes the morphological behavior of prefixes beRbased on a corpus of classical Malay. The morphological descriptions include the function, distribution and meaning of the prefix in the process of affixation with the base forms. The morphological behaviour in classical Malay is subsequently compared with that of modern Malay to observe innovation and retention in the development of the Malay language. The data used in the study comprises 2 440 258 classical Malay words generated using Telnet software from the Dewan Bahasa dan Pustaka Malay language data base. The data from modern Malay were taken from the UKM-DBP corpus comprising five million words using WordSmith Tools 5.0 software. The output data is generated in the form of a concordance and then classified and grouped based on their morphological behaviour. The data are analysed according to the generative morphology framework. The findings demonstrate that there are cases where the function, distribution, and meaning of the prefix beR- are retained, whereas in other cases it undergoes innovation, such as broadening, narrowing, substitution or elimination. Keywords: morphology, function, distribution, retention, innovation